Deskripsi Dukungan Keluarga dan Pengetahuan Ibu terhadap Praktik Pemberian ASI Eksklusif - Juliandari, Handayani; Abdi, L. Khairul; Adiyasa, I Nyoman; Irianto, Irianto (Poltekkes Kemenkes Mataram, 2023)
Background: Exclusive breastfeeding is giving only breast milk to babies aged 0-6 months without giving additional liquids such as formula milk, orange juice, honey, tea, water without additional solid foods such as bananas, papaya, porridge, milk, biscuits and Nasi Tim, but not many mothers are willing to give exclusive breastfeeding for 6 months as suggested by the world health organization (Haryono and Setianigsih, 2018). In 2018 the coverage of exclusive breastfeeding in Indonesia was 29.5% with the lowest coverage (Ministry of Health RI, 2018). Research objectives: To find out the description of family support, mother's knowledge, and exclusive breastfeeding in Sintung Village, Pringgarata District, Central Lombok Regency. Research method: The research used is analytic research with a cross-sectional approach, namely research by measuring, observing at the same time between the dependent variable and the independent variable (one time). Results: Based on the results of the study, it was concluded that there is a positive relationship between the level of knowledge of mothers and the decision to exclusively breastfeed toddlers, in other words, the lack of exclusive breastfeeding rates in Sintung Village, one of which is due to the lack of knowledge of mothers about the importance of exclusive breastfeeding for toddlers. And there is also a positive relationship between family support and the decision to exclusively breastfeed toddlers, in other words, the lack of exclusive breastfeeding in Sintung Village, one of which is due to the lack of family support for mothers who have toddlers. Research results: Based on the research conducted, it was found that out of 64 respondents, only 31 respondents (48.4%) said that toddlers in their families were exclusively breastfed. On the other hand, 33 respondents (51.6%) said that infants in their families were not exclusively breastfed. Based on the samples surveyed, it can be said that the rate of exclusive breastfeeding in Sintung Village is still not high enough. Differences in the level of knowledge of mothers significantly affect the decision of exclusive breastfeeding for toddlers, where the better the level of knowledge of mothers, there is a high tendency to provide exclusive breastfeeding for toddlers. Likewise, differences in family support significantly affect the decision to provide exclusive breastfeeding for toddlers, where with family support, there is a high tendency to provide exclusive breastfeeding for toddlers.